2023
DOI: 10.34117/bjdv9n2-098
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-modified wood sawdust waste for the removal of reactive blue II anionic dye from aqueous solution

Abstract: The Removal of an anionic Reactive Blue 2 (RB2) dye in an aqueous solution was successfully achieved using a plasma-modified agricultural biomaterial waste. Sawdust from Moabi (Baillonellatoxisperma) and Sapelli (Entandrophragmacylindricum) was modified using non-thermal gliding arc plasma. The natural raw materials and plasma treated were characterized by Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA), Scanning Electron Microscopy (SEM), XRD, Chemical analysis by Fluorescence, Sorption Analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
0
0
Order By: Relevance
“…This is due to the influence of intercalated and deposited quaternary ammonium on the interlayer clay spacing as well as the surface. These results correlate with those obtained in literature [45,49] which confirmed that the more acidic the medium, the higher the adsorption efficiency [50]. Source: Authors…”
Section: Biphenyl Adsorptionsupporting
confidence: 90%
“…This is due to the influence of intercalated and deposited quaternary ammonium on the interlayer clay spacing as well as the surface. These results correlate with those obtained in literature [45,49] which confirmed that the more acidic the medium, the higher the adsorption efficiency [50]. Source: Authors…”
Section: Biphenyl Adsorptionsupporting
confidence: 90%